Tongkat Ali Plants of Eurycoma Longifolia and Stema Tuberosa Stimulate Sexual Arousal In Domestic Cocks - Jaya Vejayan, Palliah; Yasmin Amira, Che Yahya; Srikumar, Chakravarthi; Rupbansraaj, Bathmanathan; Halijah, Ibrahim; Aida, Yun (University of Malaya, 2020)
This study compared the aphrodisiac ability of Tongkat Ali Merah (red type) or Stema tuberosato Tongkat Ali Putih (white type) or E. longifolia. Fowls dosed orally with capsule containing E. longifoliaand S. tuberosarespectively for 30 days followed by determining the efficacy by evaluating their sexual mating behavior parameters, testosterone blood level and histology of testicular tissue. Safety parameters included biochemical levels and histology of the liver. Both types of Tongkat Ali shown increases in testosterone levels (7.7±0.59 nmol/L and 6.25±0.70 nmol/L and 4.08±0.85 nmol/L; E. longifolia, S. tuberosaand control fowls, respectively) aswell as testicular histology showing seminiferous tubuleswith increased cellularity with no evidence of inflammation or fibrosis compared to the controlto indicate as testosterone boosters. All biochemical parameters tested shown to be within the control values except for alanine aminotransferaseof E. longifolia i.e. 23.50±6.36 u/L (control = 8.00±2.94 u/L). Additionally, some moderate tissue changes (focal areas of congestion of central vein and periportal scattered inflammation)were visible for the liver taken from E. longifoliatreated fowls. S. tuberosafound without any untoward effects. Tongkat Ali Merah hereby been confirmed to boost testosterone in fowls although not as effective as Tongkat Ali Putih.ABSTRAKKajian ini memperbandingkan keupayaan afrodisiak Tongkat Ali Merah atau Stema tuberosa dengan Tongkat Ali Putih atau Eurycoma longifolia. Unggas disuap dengan kapsul yang mengandungi E. longifoliadan S. tuberosaselama 30 hari bagi mengetahui keberkesanannya dengan menguji tingkah laku seksual mereka, paras darah testosteron dan histologi tisu testis. Parameter keselamatan yang diuji termasuk tahap biokimia dan histologi hati. Kedua-dua jenis Tongkat Ali menunjukkan kenaikan paras testosteron (7.7 ± 0.59 nmol / L dan 6.25 ± 0.70 nmol / L dan 4.08 ± 0.85 nmol / L; bagi E. longifolia, S. tuberosaserta unggahan kawalan, dalam urutan yang diberikan dan juga histologi testikular yang menunjukkan tubulus seminiferous dengan peningkatan selular tanpa apa-apa kesan keradangan atau fibrosis berbanding dengan kawalan iaitu membuktikan peningkatkan pengeluaran testosteron pada sel berkenaan. Semua parameter biokimia yang diuji menunjukkan pada persekitaran nilai kawalan yang juga diuji kecuali alanine aminotransferasebagi E.